Safety‐net versus private hospital setting for brain metastasis patients treated with radiosurgery alone: Disparities in follow‐up care and outcomes. Issue 1 (13th September 2017) - Diao, Kevin; Sun, Yanqing; Yoo, Stella K.; Yu, Cheng; Ye, Jason C.; Trakul, Nicholas; Jennelle, Richard L.; Kim, Paul E.; Zada, Gabriel; Gruen, John P.; Chang, Eric L.
Abstract : BACKGROUND: Stereotactic radiosurgery (SRS) alone is an increasingly accepted treatment for brain metastases, but it requires adherence to frequently scheduled follow‐up neuroimaging because of the risk of distant brain metastasis. The effect of disparities in access to follow‐up care on outcomes after SRS alone is unknown. METHODS: This retrospective study included 153 brain metastasis patients treated consecutively with SRS alone from 2010 through 2016 at an academic medical center and a safety‐net hospital (SNH) located in Los Angeles, California. Outcomes included neurologic symptoms, hospitalization, steroid use and dependency, salvage SRS, salvage whole‐brain radiotherapy, salvage neurosurgery, and overall survival. RESULTS: Ninety‐three of the 153 patients were private hospital (PH) patients, and 60 were SNH patients. The median follow‐up time was 7.7 months. SNH patients received fewer follow‐up neuroimaging studies (1.5 vs 3; P  = .008). In a multivariate analysis, the SNH setting was a significant risk factor for salvage neurosurgery (hazard ratio [HR], 13.65; P  < .001), neurologic symptoms (HR, 3.74; P  = .002), and hospitalization due to brain metastases (HR, 6.25; P  < .001). More clinical visits were protective against hospitalizations due to brain metastases (HR, 0.75; P  = .002), whereas more neuroimaging studies were protective against death (HR, 0.65; P  < .001). CONCLUSIONS: SNH patients with brain metastases treated with SRS alone had fewer follow‐up neuroimaging studies and were at higher risk for neurologic symptoms, hospitalization for brain metastases, and salvage neurosurgery in comparison with PH patients. Clinicians should consider the practice setting and patient access to follow‐up care when they are deciding on the optimal strategy for the treatment of brain metastases. Cancer 2018;124:167‐75 . © 2017 American Cancer Society . Abstract : In a retrospective cohort study of 153 patients with brain metastases, safety‐net hospital patients, in comparison with private hospital patients, received fewer total follow‐up neuroimaging studies (1.5 vs 3) and had higher rates of severe neurologic symptoms (15% vs 2%), hospitalizations due to brain metastases (25% vs 7.5%), and salvage neurosurgery (17% vs 6%) after radiosurgery alone. Clinicians should consider the practice setting and patient access to follow‐up care when they are deciding on the optimal strategy for the treatment of brain metastases.